Legal Protection for Micro, Small, and Medium Enterprises in Vacant Land Lease Agreements - Atika Sunarto; Stefani Sitinjak; Lenolewis Hiskia Purba; Muhammad Ali Adnan (Dinasti Research, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in Indonesia’s economy as they generate employment, create business opportunities, and strengthen local economic resilience. However, in contractual relationships, MSMEs are often in a disadvantaged position due to limited capital, lack of legal knowledge, and restricted access to legal assistance, making them vulnerable to losses when disputes arise with landowners. This study employs a normative juridical method with statutory, conceptual, and case study approaches. The findings indicate that, normatively, Article 1548 of the Indonesian Civil Code stipulates that a lease agreement grants the lessee the right to enjoy the benefits of the leased object with the obligation to pay rent. In practice, however, MSMEs are frequently disadvantaged due to unbalanced standard clauses or the landowner’s lack of good faith. Legal protection for MSMEs can be realized through fair contractual arrangements, mediation mechanisms for dispute resolution, and the application of the principle of legal certainty as regulated under Articles 1338 and 1243 of the Indonesian Civil Code. Providing legal protection in vacant land lease agreements is essential to ensure business sustainability and prevent exploitative leasing practices against weaker parties. The role of the state through effective regulation and supervision, as well as the enforcement of the principle of good faith by landowners, is crucial. Legal certainty is achieved when each party respects their respective rights and obligations proportionally.